2022
DOI: 10.1136/bmjopen-2021-049727
|View full text |Cite
|
Sign up to set email alerts
|

Assessing healthcare expenditures of older United States adults with pain and poor versus good mental health status: a cross-sectional study

Abstract: ObjectivesThis study aimed to determine if differences exist in healthcare expenditures of older United States (US) adults with pain based on self-reported mental health status, which is important to know given the prevalence of pain and poor mental health in the USA.DesignThis was a cross-sectional study.SettingUS Medical Expenditure Panel Survey (MEPS) interviews.ParticipantsUS adults aged ≥50 years, with self-reported pain in the past 4 weeks and positive healthcare expenditure in the 2018 Medical Expenditu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 53 publications
0
3
0
Order By: Relevance
“…The model allows adjustment for potential confounders (age, sex, marital, work, education, house income, insurance, residence, BMI, health state) to reduce residual confounders [23]. Given that the skewed distribution of outpatient and inpatient expense violated the normal distribution assumption of the regress model, logarithmic transformation was adopted in the analysis [24]. Data analyses were performed using Stata v.16.0 (StataCorp, Texas, USA).…”
Section: Discussionmentioning
confidence: 99%
“…The model allows adjustment for potential confounders (age, sex, marital, work, education, house income, insurance, residence, BMI, health state) to reduce residual confounders [23]. Given that the skewed distribution of outpatient and inpatient expense violated the normal distribution assumption of the regress model, logarithmic transformation was adopted in the analysis [24]. Data analyses were performed using Stata v.16.0 (StataCorp, Texas, USA).…”
Section: Discussionmentioning
confidence: 99%
“…The burden of disability from MSK conditions is predicted to increase due to increasing population, aging, and work-and behavior-related risk factors such as sedentary lifestyle, obesity, and injury [6]. Despite this large burden of disease and nancial cost, few studies have characterized the epidemiological burden of MSK conditions in the United States, with research mostly limited to burden of speci c conditions [11,[13][14][15][16][17]. The low number of studies on MSK disorders overall may be due to MSK disorders being perceived as rarely fatal and mostly irreversible [6].…”
Section: Introductionmentioning
confidence: 99%
“…Studies have also reported that addressing poor psychological wellbeing may be a significant approach for pain management due to its complex psychosocial aspects [ 12 ]. Although there is literature on the relationship and healthcare costs of pain and psychological wellbeing in older US adults [ 13 , 14 ], there are limited studies on the relationship among perceived pain interference and psychological wellbeing in US adults regardless of age. The primary objective of this project was to assess the association among perceived pain interference and poor psychological wellbeing in US adults.…”
Section: Introductionmentioning
confidence: 99%